Efficiency of carbon sequestering fertilizers for growth and nutrient acquisition of sunflower (Helianthus annuus L.) - Saqib, Muhammad; Tahir, Mukkram Ali; Noor-us-Sabah; Sarwar, Ghulam (Journal of Pure and Applied Agriculture, 2023)
The present work explores the assumptions that functionalized biomass derived chars (charcoal) act as carbon sequestering soil amendments to enhance the growth of sunflower. A field study was conducted at College of Agriculture, Sargodha with the aim of investigating the effect of carbon sequestering fertilizers (CSF) on growth, mineral uptake and dry matter contents of sunflower (Hysin-33). Four treatments were applied which were replicated four times using randomized complete block design (RCBD). The treatments include T1= Control (recommended NPK dose), T2= T1 + CSF (Acid treated fly ash) @ 150 kg ha -1 , T3= T1+CSF (compost powder) @ 150